A case series of necrotizing pneumonia due to community acquired MRSA - GVN Sandakumari; SD Pilapitiya; NJ Dahanayaka; MRP Weerawansa; SH Siribaddana (Anuradhapura Clinical Society, 2014)
Community-acquired pneumonia (CAP) due to Methicillin Resistant Staphylococcus Aureus (MRSA) is uncommon. In this case series, wedescribe four young immune-competent healthy males presenting with severe respiratory distress progressing to necrotizing pneumonia. All required ventilation and recovered without sequelae. One patient developed myositis and the other three developed pleural effusions and pneumothoraxes; two of them needing intercostal tube (ICT) insertion and drainage.These cases highlight community acquired MRSA in developing countries where antibiotics are frequently used empirically with little laboratory guidance.